Ergonomics risk assessment tools: A systematic review - Zayyinul Hayati, Zen; Widia, Mirta; Ezrin Hani, Sukadarin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Introduction: The ergonomic approach involves a careful examination of a job task, worker actions, and critical job information. This approach detects ergonomic risks. Identifying and managing ergonomic risk variables during risk assessment is crucial to designing and planning work activities to reduce injury risk. This study aims to investigate existing ergonomic risk assessment techniques and specific areas related to those in Ergonomic Risk Assessment (ERA) tools. Materials and methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) review technique was used to find articles on ERA tools from Scopus, PubMed, Science Direct and Google Scholar between 2010 and 2021. Twenty-two publications were selected following PRISMA guidelines based on the inclusion and exclusion criteria set. This review is divided into two sections: (1) Ergonomic Assessment Techniques and; (2) Identify specific concerned areas related to the terms Task, Individual, Load, Environmental or Other Factors (TILEO). Results: The findings address the significant ERA technique commonly utilised in the tool. The observation-based methods (67%), computer-based applications (20%), checklists, surveys and reports (10%), while the direct measurement methods (3%) of the ergonomic assessment techniques. Conclusion: It was highlighted that most ERA tools concern the task, individual and load area. Meanwhile, other factors include repetition, duration and contact stress. Furthermore, many ergonomics risk assessment tools specialise in manual materials handling tasks but focus only on assessing the physical risk factors. This review's results can help ergonomist acquire an overview of the overall ergonomic risk factors that are most likely to present in the current ergonomic risk assessment tool.